2020
DOI: 10.1021/acs.jpclett.0c01220
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Insights into the Dynamics of Growth and Degradation of All-Inorganic Perovskite Nanocrystals

Abstract: An understanding of growth and degradation pathways is significant to solve the problem of the structural instability of all-inorganic perovskite nanocrystals (NCs). However, it is still a great challenge to directly record such dynamic processes with high spatial resolution owing to the existence of complex internal factors even using in situ transmission electron microscopy observation. Here, we employ a glassy matrix to produce CsPbBr3 NCs to ensure that the growth and degradation processes of CsPbBr3 NCs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
1
17
1
Order By: Relevance
“…The crystallization process of QDs can be divided into the crystal nucleation process and crystal growth process. The grown kinetics for perovskite QDs has been previously revealed to be dominated by an Ostwald ripening process 18,36 . As the heat treatment temperature and heat treatment duration increase, the size of the QDs becomes larger, resulting in a redshift of the absorption and PL spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystallization process of QDs can be divided into the crystal nucleation process and crystal growth process. The grown kinetics for perovskite QDs has been previously revealed to be dominated by an Ostwald ripening process 18,36 . As the heat treatment temperature and heat treatment duration increase, the size of the QDs becomes larger, resulting in a redshift of the absorption and PL spectra.…”
Section: Resultsmentioning
confidence: 99%
“…The grown kinetics for perovskite QDs has been previously revealed to be dominated by an Ostwald ripening process. 18,36 As the heat treatment temperature and heat treatment duration increase, the size of the QDs becomes larger, resulting in a redshift of the absorption and PL spectra. With the increase of the heat treatment temperature and heat treatment duration, the concentration of QDs increases, the PL intensity increases first, but as the concentration of QDs further increases, the PL intensity will decrease due to the quenching effect of QDs concentration.…”
Section: Characterizationmentioning
confidence: 99%
“…[40] It was previously reported that defects in perovskite served as key flash points that could trigger structural collapse. [41] We further evaluate the stability of the perovskite films prepared under different conditions. The films are aged at 150 °C and ≈80% RH for the thermal and humidity stability tests, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal defects in CsSn­(Br 1/2 I 1/2 ) 3 could be discerned from the irregular diffraction spots marked by the circles as shown in the SAED image (Figure c). It is well-known that CsSnX 3 nanocrystals are more unstable than the lead-based perovskites, which could be degraded under the electronic irradiation of TEM . Our results also show that CsSnBr 3 nanocrystals could be destroyed during the long-term elemental mapping process (Figure S6).…”
mentioning
confidence: 99%
“…It is well-known that CsSnX 3 nanocrystals are more unstable than the lead-based perovskites, which could be degraded under the electronic irradiation of TEM. 30 Our results also show that CsSnBr 3 nanocrystals could be destroyed during the long-term elemental mapping process (Figure S6). Although stable CsSnX 3 nanocrystals were synthesized through a hot injection method, 17 their lattice structure has not been revealed ever.…”
mentioning
confidence: 99%